One-Dimensional Variational Problem on Normal Deformations with Anisotropy - Vyridis, Panayotis; Ramírez, Vianey A. Hernández (Discontinuity, Nonlinearity, and Complexity, 2026)
We study the variation along the normal direction of the deformation energy of a plane curve under the existence of an anisotropic term. The problem of variational character corresponds to a nonlinear nonhomogeneous differential equation of fourth order. This kind of problems arises from the elasticity theory, in particular from the deformation theory of elastic shells.